Top Incomes and Top Taxes in Germany - Stefan Bach; Giacomo Corneo; Viktor Steiner (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
We analyze the distribution and taxation of top incomes in Germany during the 1990s on the basis of individual tax returns data. We derive a measure of economic income from taxable gross income as reported in the tax returns. Thanks to complete sampling, we can deliver a very precise description of very high incomes, in terms of both distribution and composition by source. We also provide a measure of the effective average rate of taxation for various income groups. Our main findings are as follows: (i) incomes are highly concentrated in Germany, more than commonly thought; (ii) the German economic elite relies much less than elites in France or the US upon income from wages and salaries; (iii) income taxes are highly concentrated in Germany, more than commonly thought; (iv) although effective tax rates are significantly lower than statutory ones, the income tax is effectively progressive; (v) income taxation substantially reduces income inequality in Germany.
Keywords: D31; H24; H26; 330; Income Distribution; Personal Income Tax; Taxing the Rich; Einkommensverteilung; Reichtum; Einkommensteuer; Steuerbelastung; Deutschland